Geospatial patterns and socioeconomic determinants of the global acute viral hepatitis burden - He, Ke-Jie; Gong, Guoyu (Frontiers in Public Health, 2025)
BackgroundAcute viral hepatitis remains a persistent global health challenge, with significant morbidity and mortality associated with different hepatitis subtypes. Understanding the spatial distribution and underlying drivers of the acute hepatitis burden is crucial for developing targeted interventions.MethodsThis study leveraged data from the Global Burden of Diseases, Injuries, and Risk Factors Study to analyze the geographical disparities and temporal trends in the incidence of acute hepatitis A, B, C, and E. A multifaceted approach was employed, including spatial mapping, decomposition analysis, and frontier analysis, to elucidate the key factors shaping the epidemiological landscape.ResultsThe spatial analysis revealed pronounced global heterogeneity in acute viral hepatitis incidence, with the highest rates concentrated in parts of Africa, while Western Europe and North America exhibited significantly lower incidence levels. Decomposition analysis demonstrated that population growth was the leading driver of the increasing global burden across all hepatitis subtypes, particularly in low-SDI and low-middle SDI countries, whereas epidemiological improvements were more prominent in high-SDI countries for hepatitis B and C. Frontier analysis highlighted that countries such as Japan, South Korea, and Singapore, despite their advanced socioeconomic status, still lag behind optimal incidence thresholds, while low-SDI nations like Nepal and Burundi have made remarkable progress relative to their development level. These findings underscore considerable disparities and untapped potential for burden reduction globally.ConclusionOur findings confirm substantial spatial variation and development-related disparities in acute viral hepatitis incidence worldwide. The global burden is shaped by a combination of transmission routes, sociodemographic dynamics, and healthcare capacity. Context-specific interventions must be aligned with regional epidemiological profiles—targeting sanitation and vaccination in high-burden areas and optimizing harm reduction and screening in more developed settings. The integration of spatial analysis, decomposition, and frontier benchmarking provides a valuable framework for prioritizing national and global hepatitis control strategies.